IMF Staff papers : Volume 40 No. 3. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1993)
This paper assesses alternative auction techniques for pricing and allocating various financial instruments, such as government securities, central bank refinance credit, and foreign exchange. Before recommending appropriate formats for auctioning these items, the paper discusses basic auction formats, assessing the advantages and disadvantages of each, based on the existing, mostly theoretical, literature. It is noted that auction techniques can be usefully employed for a broad range of items and that their application is of particular relevance to the impetus in many parts of the world toward establishing market-oriented economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet